(untitled) (Dermatology Reports, 2025)
Basal cell carcinoma (BCC) treatment aims to completely remove the tumor, maintain skin function, and restore appearance. Tumor removal can result in various patterns of abnormalities, depending on the size and location. The integration of advancement and interpolation flaps ensures adequate coverage without tension or distortion for substantial defects involving multiple cosmetic subunits. A 43-year-old female patient with basal cell carcinoma presented with a large periorbital tumor affecting multiple cosmetic subunits. Reconstruction was optimally achieved through a combination of advancement and interpolation flaps, successfully restoring both aesthetic appearance and skin function.